Misi Gereja Menghadirkan Kerajaan Allah di Bumi - I Made Priana (SANCTUM DOMINE: JURNAL TEOLOGI, 2016)
This article tries to show that the mission of the church is to present or to embody the kingdom of God in this earth. The kingdom of God mission is not church oriented mission but the world oriented mission. The kingdom of God mission is God’s mission which is done by Jesus that the world will exist and run as it is designed by God, that is the world under God’s sovereignty. As God sent Jesus to present the kingdom of God in this earth, it does likewise Jesus sends the church to actualize the mission of Jesus (John 20:21). Church mission is actualization of Jesus’mission that is by words and deeds demonstrating the values of the kingdom of God that the world will be transformed as it is designed by God.